A cationic cyclodextrin derivative-lipid hybrid nanoparticles for gene delivery effectively promotes stability and transfection efficiency. (2nd January 2022) - Wang, Zhongjuan; Xu, Shaobin; Xia, Hongying; Liu, Yanqiu; Li, Bin; Liang, Yueqin; Li, Zhongkun
Abstract: Genetic medicines hold great promise for treatment of a number of diseases; however, the development of effective gene delivery carrier is still a challenge. The commonly used gene carrier liposomes and cationic polymers have limited their clinical application due to their respective disadvantages. Lipid–polymer hybrid nanoparticles (LHNPs) are novel drug delivery system that exhibit complementary characteristics of both polymeric nanoparticles and liposomes. In this account, we developed the α-cyclodextrin-conjugated generation-2 polyamidoamine dendrimers–lipids hybrid nanoparticles (CDG2-LHNPs) for gene delivery. The pDNA/CDG2-LHNPs was stable during 15 days of storage period both at 4 °C, 25 °C, and 37 °C, whereas the particle size of pDNA/CDG2 and pDNA/liposomes dramatically increased after storage at 4 °C for 8 h. CDG2-LHNPs showed significantly superior transfection efficiencies compared to either CDG2 or liposomes. The mechanism of high transfection efficiency of pDNA/CDG2-LHNPs was further explored using pharmacological inhibitors chlorpromazine, filipin, and cytochalasion D. The result demonstrated that cell uptake of pDNA/CDG2-LHNPs was mediated by clathrin-mediated endocytosis (CME), caveolae-mediated endocytosis (CvME), and macropinocytosis together. pDNA/CDG2-LHNPs were more likely be taken up by cells through CvME, which avoided lysosomal degradation to a large extent. Moreover, the liposome component of pDNA/CDG2-LHNPs increased its cell uptake efficiency, and the CDG2 polymer component increased its proton buffer capacity, so the hybrid nanoparticles taken up by CME could also successfully escape from the lysosome. CDG2-LHNPs with stability and high-transfection efficiency overcome the shortcomings of liposomes and polymers applied separately, and have great potential for gene drug delivery.